ENVIRONMENTAL AND SOCIAL INJUSTICE: IMPACT AND SUSTAINABILITY OF SMALL SCALE TIN MINING UNDER INDONESIA’S NEW MINERAL AND COAL REGULATION - Derita Prapti Rahayu; Faisal Faisal; Darwance Darwance; Komang Jaka Ferdian (Cepalo, 2023)
The transformation of mining law policy in Law No. 3 of 2020 concerning Minerals and Coal has broad implications for mining law, including illegal tin mining. The high dependence of the tin extractive economy in Bangka Belitung has changed the landscape of this archipelago province as an area with a high level of natural damage and social disasters. The ability of governments through regulatory instruments to tackle illegal mining is an important ideal goal. This research was conducted using socio-legal methods, to produce a comprehensive analysis related to the environmental and social impacts of illegal tin mining after the renewal of the mineral and coal law. This study found that the transition of mining authority from the central government to the regional government directly has an impact on the proliferation of illegal mining activities. Substantive changes in the mineral and coal law have not provided a strategic solution because the tug-of-war over authority ends with the continued delegation of authority to grant community mining permits to local governments. Meanwhile, the unpreparedness of local governments has resulted in the continued marginalization of mining communities and has an impact on widespread environmental damage. The lack of fair decision-making processes for people mining licences is indicative of an immature tin mining management in Bangka Belitung. The purpose of this study is to provide a comprehensive overview of the implications of the latest mineral and coal policies on illegal tin mining activities, as a reference and consideration in strategic policy making to create an ideal and sustainable tin mining ecosystem.